The effect of tax avoidance, sustainbility report, corporate governance on firm value: Leverage as moderating (Empirical Study On Registered Manufacturing Companies On the Indonesia Stock Exchange 2014-2019) - Andayani, Endro; Yanti, Harti Budi (Technium Social Sciences Journal, 2021)
Disclosure about the factors that influence firm value is the aim of this study. Tax avoidance variables, sustainability reports, corporate governance practices and leverage are thought to influence firm value. Samples were selected based on certain criteria. Therefore, data obtained from the Indonesia Stock Exchange as many as forty companies for six years (2014 to 2019). The results reveal that tax avoidance, sustainability reporting, corporate governance practices affects firm value in a negative direction. Meanwhile, leverage affects firm value in a positive direction. The effect of the sustainability report on firm value is proven not to be strengthened by the leverage variable as a moderating variable, but it does strengthen the effect of tax avoidance and corporate governance on firm value.. Originality / Value - This paper contributes to three different series of studies: the literature on government as a determinant of tax avoidance in Indonesia. For companies, evaluate, improve, improve performance. For investors, to assist in making wise judgments about the value of the firm, it is worth considering other factors and for the academy as the theoretical library used. For further research with institutional ownership variable, financial crisis as a moderating variable.